Splinting after Distal Radius Fracture Fixation: A Prospective Cohort Analysis of Postoperative Plaster Splint versus Soft Dressing - Poiset, Spencer; Abboudi, Jack; Gallant, Gregory; Jones, Christopher; Kirkpatrick, William; Kwok, Moody; Liss, Frederic; Rivlin, Michael; Takei, T. Robert; Wang, Mark; Ilyas, Asif M. (Journal of Wrist Surgery, 2019)
Background The effect of postoperative dressing and splinting after distal radius fracture (DRF) open reduction internal fixation (ORIF) is not well understood. A prospective cohort analysis was performed to assess differences in functional and radiographic outcomes with the use of plaster splinting or soft dressing following DRF ORIF.Methods All patients undergoing DRF ORIF with locking volar plates were consecutively enrolled. Preoperative demographic and postoperative radiographic and functional outcome data were collected at 2 weeks and 3 months postoperatively. Functional data included range of motion (ROM), pain on visual analog scale (VAS), Patient-Rated Wrist Evaluation (PRWE), and quick Disabilities of the Arm, Shoulder and Hand (DASH) scores. Radiographic data included loss of fracture reduction.Results A total of 139 patients were enrolled (79 plaster splinting, 60 soft dressing). By the first postoperative visit (POV), there was one case of loss of reduction with plaster splinting and one case with soft dressing with no hardware failure or revision surgery in either group, and no difference in DASH, PRWE, or VAS pain scores. By the final POV, the soft dressing group showed greater ROM in extension by 9.6, flexion by 10.9, and supination by 4.8 degrees over plaster splinting. Additionally, the soft dressing group demonstrated statistically significant improvement in PRWE and DASH scores, as well as VAS pain scores as compared with plaster splinting.Conclusions Applying only soft dressing following DRF ORIF demonstrated improvements in ROM, VAS, and functional outcomes by final follow-up, with no significant differences in radiographic outcomes. No benefit of applying a plaster splint was identified.
Keywords: distal radius; fracture; DRF; open reduction internal fixation; ORIF; volar plates; wrist surgery; postoperative; splint; soft dressing; prospective; cohort